Modified 30 G needle trypan blue staining technique under air for a uniform and consistent anterior capsule staining - Om Parkash R (Dove Medical Press, 2017)
Rohit Om Parkash, Shruti Mahajan, Tushya Om Parkash Dr Om Parkash Eye Institute, Amritsar, India Purpose: To describe a trypan blue dye staining technique under air, a modification of the previously described 30 G needle under-air technique.Design: This is a prospective, randomized study of 1,000 eyes of 952 patients undergoing phacoemulsification in a private practice setting from January 2015 to August 2016. Three variants as a modification of the previously known 30 G needle technique are described. In our technique, after injecting one drop of the dye under air, the needle is kept in the anterior chamber (AC) for 15 seconds. In the second variation, along with the additional hold time, 0.05 mL air is injected prior to dye injection to deepen the AC in eyes with shallow ACs or in cases with increased posterior pressure. The third variation is the selective painting approach in which more than one drop is injected for a homogenous staining.Main outcome measures: The main outcome measures were safety and reproducibility of the technique along with homogeneity and uniformity of the anterior capsule staining.Results: AC remained stable during the hold time of 15 seconds with no egress of air. No iatrogenic trauma occurred in any of the cases. All cases had a homogeneously stained anterior capsule. The staining intensity was excellent in 80.8% of the eyes and good in 19.2% of the eyes.Conclusion: This is a safe, simple, and cost-effective technique which achieves consistent, uniform, and reproducible staining. It overcomes the shortcomings of the known 30 G needle technique. Keywords: trypan blue staining, anterior capsule staining, under air, 30 G needle technique, effective staining, uniform staining